Imaging of the Achilles tendon in spondyloarthritis: a comparison of ultrasound and conventional, short and ultrashort echo time MRI with and without intravenous contrast. - Hodgson, R; Grainger, A; O'Connor, P; Evans, R; Coates, L; Marzo-Ortega, H; Helliwell, P; McGonagle, D; Emery, P; Robson, M (2011)
OBJECTIVES: To compare conventional MRI, ultrashort echo time MRI and ultrasound for assessing the extent of tendon abnormalities in spondyloarthritis. METHODS: 25 patients with spondyloarthritis and Achilles symptoms were studied with MRI and ultrasound. MR images of the Achilles tendon were acquired using T1-weighted spin echo, gradient echo and ultrashort echo time (UTE) sequences with echo times (TE) between 0.07 and 16 ms, before and after intravenous contrast medium. Greyscale and power Doppler ultrasound were also performed. The craniocaudal extent of imaging abnormalities measured by a consultant musculoskeletal radiologist was compared between the different techniques. RESULTS: Abnormalities were most extensive on spoiled gradient echo images with TE = 2 ms. Contrast enhancement after intravenous gadolinium was greatest on the UTE images (TE = 0.07 ms). Fewer abnormalities were demonstrated using unenhanced UTE. Abnormalities were more extensive on MRI than ultrasound. Contrast enhancement was more extensive than power Doppler signal. CONCLUSIONS: 3D spoiled gradient echo images with an echo time of 2 ms demonstrate more extensive tendon abnormalities than the other techniques in spondyloarthritis. Abnormalities of vascularity are best demonstrated on enhanced ultrashort echo time images.